Discrimination of pathological voices using systole activated neural network - Murugesa Pandiyan, Paulraj, Prof. Madya Dr; Sazali, Yaacob, Prof. Dr.; Hariharan, Muthusamy, Dr. (Noise, Vibration and Comfort Research Group, 2012)
Proceedings of the Regional Conference on Engineering Mathematics, Mechanics, Manufacturing & Architecture (EM3 ARC) 2007 was jointly organized by Universiti Kebangsaan Malaysia (UKM), 27th - 28th November 2007 at Kuala Lumpur, Malaysia.